ENERGY AND ENVIRONMENTAL EFFICIENCY OF CONTEMPORARY INTERIOR DESIGN UNDER GEOCLIMATIC CHANGES - PLATON, L. (Art and Design, 2024)
The aim of the paper is to determine the means of energy efficiency in interior design and classify them according to the type of room and the comfort needs of contemporary society. Methodology. The research methodology initially proposes an analysis, deduction and synthesis of the scientific works developed until now in the direction of energy efficiency in the field of architecture and construction. Based on them, a deduction from general to particular of the materials and practical solutions used in the interior design is elaborated. Results. The research results highlight practical solutions and recommendations for ecological and energy-efficient interior design. The recommendations are classified by types of materials used in the interior design but also by design solutions in accordance with the type and purpose of the room. The scientific results obtained demonstrate the role and importance of eco-design in the current conditions of climate change and ecological degradation detected in the natural environment. The recommendations provide for the development and promotion of eco-design in the specialized field as a means of energy efficiency and conservation of the natural ecosystem. The proposed solutions are argued by describing the opportunities and advantages of ecological materials for human life and quality of life. They are also argued by identifying the protection processes of the natural ecological system. The results of the research determine the Eco-design solutions through the major contribution in the reduction of toxic waste, the gradual cleaning of the natural ecosystem, the increase of energy efficiency in homes and the provision of interior comfort. Scientific novelty of the material lies in the structuring and classification of ecological design solutions in people's ordinary homes. Determining and identifying the function of eco-design and its role in ensuring the energy efficiency of the indoor environment. Practical significance of the study is argued in the section "Eco-design. Eco solutions in interior design" which describes ecological solutions and materials for contemporary interior design.